Encyclopedia of capital punishment in the United States - Palmer, Louis J. (McFarland, 2008)
"In this updated encyclopedia are entries on virtually every capital punishment decision rendered by the U.S. Supreme Court from its inception through 2006. Entries are also provided for each Supreme Court Justice who has ever rendered a capital punishment opinion. Entries on jurisdictions cite present-day death penalty laws and judicial structure"--Provided by publisher